Analysis of Commercial and Fiscal Profits, Leverage on Profit Persistence at PT. Mighty True Great - Nurwahyuni Nurwahyuni; Faradita Farid; Anna Nurjanna; Indri Apriani; Muh. Asrullah Arifin; Vivianty Hemeto; Nungki Prawitasari; Muhammad Zidane Alfarizi (Jurnal Ilmu Manajemen Profitability, 2024)
This study, titled "Analysis of Commercial and Fiscal Profits, Leverage on Profit Persistence at PT. Mighty True Great," aims to investigate the impact of differences in commercial and fiscal profits, leverage, and their combined effects on profit persistence at PT. Mighty True Great. The research employs quantitative methods and utilizes financial statements from 2017 to 2019 for data analysis. Financial statements serve as a crucial tool for conveying a company's financial status to various stakeholders. Profit quality, particularly profit persistence, is an essential component in assessing a company's performance and making informed decisions. The study focuses on the phenomenon of differences between accounting profits and fiscal profits, known as Book-Tax Differences, and how these differences influence profit persistence. The research explores the role of leverage in shaping financial statements and its potential impact on profit persistence. Leverage, represented by the Debt to Equity Ratio, is highlighted as a significant factor affecting profit persistence. The study specifically investigates PT. Mighty True Great, a company operating in the animal feed industry, and analyzes its profit trends and the influence of leverage on profit persistence. The findings reveal that differences in commercial and fiscal profits, both temporary and permanent, have no significant impact on profit persistence at PT. Mighty True Great. However, the study identifies that leverage has a notable influence on profit persistence, suggesting that the company's debt levels affect its ability to sustain profits over time. In conclusion, the research emphasizes the importance of companies paying attention to profit stability and persistence. For future studies, researchers are encouraged to explore additional variables that may impact profit persistence and extend the observation period to provide a more comprehensive understanding. The recommendations aim to guide companies in decision-making and offer valuable insights for potential investors considering the persistence of a company's profits.